Drug Metabolism/Transport and Pharmacokinetics - Song, Im-Sook (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book serves to highlight the pharmacokinetics/drug-drug interactions and mechanistic understanding in relation to the drug-metabolizing enzymes and drug transporters.This book presents a series of drug metabolism and transport mechanisms that govern the pharmacokinetic features of therapeutic drugs as well as natural herbal medicines. It also covers the pharmacokinetic interactions caused by inhibiting or inducing the metabolic or transport activities under disease states or the coadministration of potential inhibitors. It also deals with microenvironmental pharmacokinetic profiles as well as population pharmacokinetics, which gives new insights regarding the pharmacokinetic features with regard to drug metabolism and transporters.